2012
DOI: 10.5740/jaoacint.sge_dinc
|View full text |Cite
|
Sign up to set email alerts
|

A New Application of Continuous Wavelet Transform to Overlapping Chromatograms for the Quantitative Analysis of Amiloride Hydrochloride and Hydrochlorothiazide in Tablets by Ultra-Performance Liquid Chromatography

Abstract: A new application of continuous wavelet transform (CWT) to overlapping peaks in a chromatogram was developed for the quantitative analysis of amiloride hydrochloride (AML) and hydrochlorothiazide (HCT) in tablets. Chromatographic analysis was done by using an ACQUITY ultra-performance LC (UPLC) BEH C18 column (50 x 2.1 mm id, 1.7 pm particle size) and a mobile phase consisting of methanol-0.1 M acetic acid (21 + 79, v/v) at a constant flow rate of 0.3 mL/min with diode array detection at 274 nm. The overlappin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…(4) Flexibility in selecting bases. Because wavelet transform can flexibly select transform bases, for different applications and different research objects, different wavelet mother functions can be selected to obtain the best results [17], [18].…”
Section: Ct Image Denoising Processing Technology Based On Wavelementioning
confidence: 99%
“…(4) Flexibility in selecting bases. Because wavelet transform can flexibly select transform bases, for different applications and different research objects, different wavelet mother functions can be selected to obtain the best results [17], [18].…”
Section: Ct Image Denoising Processing Technology Based On Wavelementioning
confidence: 99%
“…Nevertheless, the CWT method is not without flaws. This method produces chromatograms analogous to second derivative analysis, so the focus is more on peak detection rather than profile determination, although some studies have shown that areas can be extracted and calibration curves can be obtained [79,80]. The CWT needs to be optimized in terms of the selection of the appropriate wavelet function as well as the scale factor.…”
Section: Continuous Wavelet Transformation (Cwt)mentioning
confidence: 99%
“…As a variety of isomers exist, the total ion chromatogram (TIC) peaks of diisononyl ortho-phthalate (DINP) and diisodecyl ortho-phthalate (DIDP) are seriously overlapped and noisy, 3,4,13,14 and this leads to difficulty when qualifying and quantifying DINP and DID. It is reported that wavelet transforms can be used for resolution of overlapping chromatographic peaks, [15][16][17][18] although there is no report about its applications for resolution of overlapping chromatographic peaks in GC-MS analysis of PAEs, except that we recently used continuous wavelet transform (CWT) [19][20][21][22][23][24] for resolution of the overlapped TIC peaks of DINP and DIDP when investigating migration behaviors of PAEs from food packaging materials to fatty food simulants. 25 It shows that CWT can be used to "mathematically" resolve the overlapped noisy peaks.…”
Section: Introductionmentioning
confidence: 99%